2015
DOI: 10.1002/nme.5136
|View full text |Cite
|
Sign up to set email alerts
|

A ‘nodeless’ dual superelement formulation for structural and multibody dynamics application to reduction of contact problems

Abstract: Summary A ‘nodeless’ superelement formulation based on dual‐component mode synthesis is proposed, in which the superelement dynamic behavior is described in terms of modal intensities playing the role of intrinsic variables. A computational scheme is proposed to build an orthogonal set of static modes so that the system matrices can have a diagonal or nearly diagonal form, providing thus high computational efficiency for application in the context of structural dynamics as well as flexible multibody dynamics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Cardona 17 and Wu and Tiso 18 combined CraigBampton modes with the floating frame concept to reduce the coordinates of flexible structure models. Ge´radin and Rixen 19 used MacNeal modes to simulate structures with unilateral contacts, such as leaf springs.…”
Section: Introductionmentioning
confidence: 99%
“…Cardona 17 and Wu and Tiso 18 combined CraigBampton modes with the floating frame concept to reduce the coordinates of flexible structure models. Ge´radin and Rixen 19 used MacNeal modes to simulate structures with unilateral contacts, such as leaf springs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the already reduced model could be further reduced by a modal truncation approach, as followed by Novotny [17] for elastic journal bearings. In addition, a load dependent approach by using free interface normal modes and attachment modes could have been followed (see [18][19][20]). …”
Section: Reduction Methodologymentioning
confidence: 99%
“…When terms including W 1 , W 2 and W 3 can be neglected, the simulation time decreases significantly in cases where models with a high number of flexible bodies and/or when flexible bodies with many modes are considered. Note that the latter becomes more and more relevant because there is a tendency to consider more and more local effects in flexible multibody dynamics (see, for example, [18][19][20][21] and [26]). In order to illustrate the potential, two examples are given.…”
Section: Benefitmentioning
confidence: 99%
“…In the literature two approaches can be found that deal with the question of which terms need to be considered and which need not. The first one is the strict application of a small deformation assumption at the level of the kinetic energy; see, for example, [12] or [21]. With this assumption, a remarkably simple set of equations is obtained.…”
Section: Introductionmentioning
confidence: 99%